Formation of Super‐Assembled TiOx/Zn/N‐Doped Carbon Inverse Opal Towards Dendrite‐Free Zn Anodes. Issue 7 (27th December 2021) - Sun, Peng Xiao; Cao, Zhenjiang; Zeng, Yin Xiang; Xie, Wen Wen; Li, Nian Wu; Luan, Deyan; Yang, Shubin; Yu, Le; Lou, Xiong Wen (David)
Abstract: Uncontrolled growth of Zn dendrites and side reactions are the major restrictions for the commercialization of Zn metal anodes. Herein, we develop a TiO x /Zn/N‐doped carbon inverse opal (denoted as TZNC IO) host to regulate the Zn deposition. Amorphous TiO x and Zn/N‐doped carbon can serve as the zincophilic nucleation sites to prevent the parasitic reactions. More importantly, the highly ordered IO host homogenizes the local current density and electric field to stabilize Zn deposition. Furthermore, the three‐dimensional open networks could regulate Zn ion flux to enable stable cycling performance at large current densities. Owing to the abundant zincophilic sites and the open structure, granular Zn deposits could be realized. As expected, the TZNC IO host guarantees the steady Zn plating/stripping with a long‐term stability over 450 h at the current density of 1 mA cm −2 . As a proof‐of‐concept demonstration, a TZNC@Zn||V2 O5 full cell shows long lifespan over 2000 cycles at 5.0 A g −1 . Abstract : A TiO x /Zn/N‐doped carbon inverse opal (TZNC IO) structure is designed through a multi‐step method to regulate Zn deposition for Zn metal anodes. Benefitting from the ordered open structure with abundant zincophilic sites, the TZNC host can realize a preferential Zn nucleation and growth in the confined space. As expected, the dendrite‐free TZNC@Zn composite anode enables long‐term cycling in both symmetric and full cells.